CLOSE UP - Quick, Amanda (New York : A JOVE BOOK, 2020)
Welcome to Burning Cove, California where 1930s Hollywood glamour conceals a ruthless killer... Vivian Brazier never thought life as an art photographer would include headshots for aspiring celebrities or nightly calls to take snaps of grisly murders... When she's called to take photos of a famous actress, the latest victim of the 'Dagger Killer', Vivian notices eerie similarities to previous crime scenes. Details that only a photographer would have noticed. Details that put Vivian right at the top of the killer's target list. Nick Sundridge has always been able to 'see' things that others don't. His talent, along with his dark past, makes him a recluse, but a brilliant investigator. When Nick is sent to protect Vivian, together they discover that the Dagger Killer has ties to the glitz and glamour of Hollywood royalty and high society. It's a cut-throat world of allure and deception that Vivian and Nick must traverse in order to uncover the killer who willl stop at nothing to add them to their gallery of murders...
"Jayne Ann Krentz wrigin as Amanda Quick"--Cover.
Keywords: Murder -- Investigation -- Fiction; Serial murders -- Fiction; Photographers -- Fiction